PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SD NEGERI 29 PEKANBARU - Gusti Elpida; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The research was motivated by the low learning outcomes of science students in grade VB SD Negeri 29 Pekanbaru on subjects IPA. We can be seen from the KKM set by the school which is 75, from 36 students who reached KKM were 20 people (55,55%) and those who did not reach KKM were is 16 people (44,44%) with a class average is 70,69. The research aims to increase student achievement learning on the subject of IPA in class VB students of SD Negeri 29 Pekanbaru. The research is a kind of classroom action research. Data collection techniques is learning outcomes test and observation sheets. The test is used to collect student learning outcomes data, while the observation sheet is used to collect data on student and teacher activities. Learning outcomes before being given an action are indicated by a percentage of completeness of 55,55%. Learning outcomes after being given action in the first cyle experienced an increase 72,22% and an increase in the second cyle was 88,88%. Based on the results of the study it can be concluded that the application of the models problem based learning (pbm) can improve student achievement learning on the subject of IPA in class VB SD Negeri 29 Pekanbaru.Keyword : Problem Based Learning model, Study result of IPA